2008
DOI: 10.1124/dmd.108.023101
|View full text |Cite
|
Sign up to set email alerts
|

Deferiprone Glucuronidation by Human Tissues and Recombinant UDP Glucuronosyltransferase 1A6: An in Vitro Investigation of Genetic and Splice Variants

Abstract: ABSTRACT:Tissue iron overload constitutes a major health problem for people who require regular blood transfusions, such as those with ␤-thalassemia major. Deferiprone is a hydroxypyridinone iron chelator used therapeutically to remove this excess iron and prevent tissue damage. Deferiprone is metabolized by UDP-glucuronosyltransferases (UGTs) into deferiprone 3-O-glucuronide (DG), but a systematic evaluation of the contribution of individual human UGTs and the impact of genetic variations of UGTs have not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…In contrast to a previous study that showed recombinant UGT1A10 homogenates have greater activity compared with UGT1A10 microsomes for a variety of substrates, including tamoxifen Sun et al, 2007), we observed that microsomes are more active for fenofibrate than homogenates, suggesting that such differences could be substrate-specific. A higher activity with microsomes compared with Supersomes was also observed, as noted in other studies (Benoit-Biancamano et al, 2009). Thus, a primary role of UGT2B7 followed by UGT1A9 and possibly UGT1A3 in the hepatic clearance of FA is predicted and further supported by correlative studies using liver microsomes and UGT probe substrates.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to a previous study that showed recombinant UGT1A10 homogenates have greater activity compared with UGT1A10 microsomes for a variety of substrates, including tamoxifen Sun et al, 2007), we observed that microsomes are more active for fenofibrate than homogenates, suggesting that such differences could be substrate-specific. A higher activity with microsomes compared with Supersomes was also observed, as noted in other studies (Benoit-Biancamano et al, 2009). Thus, a primary role of UGT2B7 followed by UGT1A9 and possibly UGT1A3 in the hepatic clearance of FA is predicted and further supported by correlative studies using liver microsomes and UGT probe substrates.…”
Section: Discussionsupporting
confidence: 74%
“…Tacrolimus (200 mM, 60 minutes) was obtained from Cell Signaling Technologies (Danvers, MA). Glucuronides were measured by mass spectrometry-based methods (Lepine et al, 2004;Benoit-Biancamano et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…A proportion of the variability of UGT1A1 expression in the population is due to the common variable number tandem repeat polymorphism in the UGT1A1 gene promoter associated with Gilbert's syndrome (Bosma et al, 1995;Monaghan et al, 1996) [or other mutations in different populations, e.g., Koiwai et al (1995))]; however, measurements of mRNA levels show very wide interindividual variation for all UGTs [e.g., Izukawa et al (2009))], suggesting that other environmental, genetic, and/or epigenetic factors significantly affect expression levels. UGT1A6 is responsible for the glucuronidation of many xenobiotics, and several drugs are known to be substrates for this enzyme, including paracetamol (Court et al, 2001), valproate , and deferiprone (Benoit-Biancamano et al, 2009). UGT1A6 also metabolizes several important endogenous substrates such as serotonin (Krishnaswamy et al, 2004).…”
Section: Downloaded Frommentioning
confidence: 99%